Adhesion and marginal adaptation of a claimed bioactive, restorative material. Issue 1 (20th December 2019) - Benetti, Ana Raquel; Michou, Stavroula; Larsen, Liselotte; Peutzfeldt, Anne; Pallesen, Ulla; van Dijken, Jan Willem Viator
Abstract: Objectives: Adhesion and marginal adaptation of a claimed bioactive restorative material (ACTIVA BioACTIVE Restorative) to human teeth were compared with those of a resin-modified glass ionomer cement (Fuji II LC) and a control resin composite (Ceram X Mono). Material and Methods: Shear bond strength and marginal adaptation to enamel and dentine were assessed after no pretreatment of the hard tissues or after etching with phosphoric acid (ACTIVA BioACTIVE Restorative and Ceram X Mono) or polyacrylic acid (Fuji II LC). For ACTIVA BioACTIVE Restorative, the effect of applying a self-etch adhesive (Xeno Select, Dentsply Sirona) was also investigated. Data were analyzed using non-parametric tests ( α  = 0.05). Results: Bond strength and marginal adaptation in enamel and dentine were significantly different among the investigated materials ( p <.05). Due to loss of restorations, it was not possible to measure bond strength of ACTIVA BioACTIVE Restorative if no pretreatment was performed or if dentine was etched; however, use of the self-etch adhesive resulted in similar bond strength as Ceram X Mono. Etching improved adhesion of Fuji II LC to enamel and dentine. Regarding marginal adaptation, ACTIVA BioACTIVE Restorative showed the highest wall-to-wall contraction to enamel in all pretreatment groups and the overall highest wall-to-wall contraction to dentine after etching. Due to loss of restorations, no marginal assessment was possible on cavities with margins in dentine when no pretreatment was used. The use of a self-etch adhesive with ACTIVA BioACTIVE Restorative resulted in similar adaptation to dentine compared to the other materials. Conclusion: The self-adhesive property of ACTIVA BioACTIVE Restorative is nonexistent.